Modeling of the in-pipe inspection robot: a comprehensive review - Shaikh Salim, Sheikh Ahmad Zaki; Mohd Yakub, Mohd Fitri; Ab Rashid, Mohd Zamzuri; Syed Mohd Putra, Sharifah Munawwarah; Roslan, Shairatul Akma; Mamat, Normaisharah M. (Elsevier Ltd, 2020)
The in-pipe inspection robotic system is crucial in examining the inside of a pipe without compromising its structural safety. The in-pipe inspection robotic system is a promising alternative to conventional methods of xray inspection and visual inspection. Despite the ongoing investigation, the effectiveness of the in-pipe inspection robotic system, particularly regarding the mathematical modeling of the system design, still needs to be improved. The in-pipe inspection robot which is normally equipped with a camera or non-destructive testing (NDT) equipment moves inside the pipeline to conduct a pipe integrity assessment. The main problem during an inspection is the restricted maneuverability of the robot due to geometric changes in the pipe. This can be overcome by designing a proper mathematical model to develop an effective inspection robotic system. Therefore, this paper provides a systematic review of different modeling types of the in-pipe inspection robotic systems, including the assessment of the kinematic and dynamic mathematical models for the system. This review paper covers in-pipe inspection robotic systems with several driving mechanisms such as fluid-driven, wheeled mobile drive (WMD), screw or helical drive, legged and biomimetic drives.